Tinjauan Yuridis Pelanggaran Cyber Attack Dalam Perang Modern Berdasarkan Hukum Humaniter Internasional - Stenly Pattiruhu; Johanis Steny Franco Peilouw; Wilshen Leatemia (Faculty of Law Pattimura University, 2022)
Introduction: Violations in the form of cyber attacks are carried out by countries that have strong cyber space infrastructure against other countries that have weaknesses in their cyber defense systems.Purposes of the Research: The purpose of this paper is to find out and understand the position of cyber attacks in international humanitarian law and to know and understand the state's responsibility for the use of cyber attacks. Methods of the Research: This type of research is normative juridical where the research is carried out by collecting primary, secondary and tertiary data obtained using library research. The data that has been collected is analyzed qualitatively, the description of which is arranged systematically based on legal disciplines to achieve clarity on the issues to be discussed.Results of the Research: The results of this study indicate that the position of cyber attacks in international humanitarian law is the same as conventional wars based on a cyber attack approach as a war domain as well as attacks in cyber attacks. Cyber attacks also violate the principles of humanitarian law, namely the Principle of Discrimination, the Principle of Proportionality and Uncessary Suffering. Furthermore, with regard to the state having an obligation to be responsible for violations of the principles of International Humanitarian Law caused by cyber attacks carried out by a person or group, it is proven to have a close relationship with the state in accordance with international customs regarding state responsibilities and is also obliged in the responsibilities contained in the law. United Nations Charter. Forms of liability can be in the form of cessation of attacks and reparations. The reparations themselves can be carried out by means of restitution, compensation and giving satisfaction to the victim country.